Effect of Electrical Heat Carrier Temperature on Bacterial Leakage of Endodontically Treated Teeth Using a Bioceramic Sealer - Mir Ahmad Nabavi; Mahmood Reza Kalantar Motamedi; Pedram Fattahi; Saber Khazaei (Clinical and Experimental Dental Research)
ABSTRACT Objectives The aim of this study is to investigate the effect of electrical heat carrier temperature on bacterial leakage of root canals obturated with the continuous wave of condensation (CWC) technique and a bioceramic sealer. Methods This ex vivo experimental study was conducted on 92 extracted single‐rooted teeth. The teeth were subjected to endodontic treatment and obturated with the Endoseal MTA bioceramic sealer by the CWC technique using two different temperature settings of the electrical heat carrier: 120°C (group G120, n = 41) and 200°C (group G200, n = 41). A positive and a negative control group were also considered (n = 5 each). Bacterial leakage was assessed over a 40‐day period using a bacterial leakage model. The incidence of bacterial leakage was compared between the experimental groups using the log‐rank test. The significance level was set at 0.05. Results The median survival rate was 39.0 (25.0) days in the G120 group and 34.0 (25.0) days in the G200 group. Despite a slightly higher survival rate in the G120 group, the difference between the two experimental groups was not statistically significant (p = 0.612). Conclusion The tested temperatures of the electrical heat carrier (120°C and 200°C) did not have a significant effect on bacterial leakage of root canals obturated by the CWC technique and the Endoseal MTA bioceramic sealer.